How to Cope With Strategic Infrastructure Disparities in West Java? (A Post-Pandemic Economic Recovery Analysis ) - Satya Laksana; Angga Muchlish Al Rahmat (Pusbindiklatren Bappenas, 2022)
The availability of energy and telecommunication facilities has been claimed as two strategic infrastructures supporting the West Java economy during and the post-pandemic. However, researchers found that the West Java electricity and telecommunication infrastructure is inter-regionally inequitable. This paper aims to identify the recent electrical energy access of households and the existing condition of telecommunication infrastructure; to configure the investment data in the last five years, and to analyze the opportunities and challenges of investment, and development of electricity and telecommunication network in the future. This research uses the Desk Study method by collecting primary data from bureaucrats and secondary data from relevant Government agencies. The results show that electricity and telecommunications infrastructure conditions in West Java are still unequal between the Northern and Southern regions, particularly in terms of electrification ratio, cellular phone signal strength, and internet signal quality. Furthermore, investment in West Java was very unequal, with about two-thirds of foreign and domestic investment in Bekasi and Karawang districts in the last-five-years. This study formulates recommendations for policy in the investment, electricity, and telecommunications sectors in dealing with interregional infrastructure development disparities as well as economic challenges during and after the pandemic.